Cellular Biology of Tau Diversity and Pathogenic Conformers - Kang, Sang-Gyun; Eskandari-Sedighi, Ghazaleh; Hromadkova, Lenka; Safar, Jiri G.; Westaway, David (Frontiers in Neurology, 2020)
Tau accumulation is a prominent feature in a variety of neurodegenerative disorders and remarkable effort has been expended working out the biochemistry and cell biology of this cytoplasmic protein. Tau’s wayward properties may derive from germline mutations in the case of frontotemporal lobar degeneration (FTLD-MAPT) but may also be prompted by less understood cues - perhaps environmental or from molecular damage as a consequence of chronological aging - in the case of idiopathic tauopathies. Tau properties are undoubtedly affected by its covalent structure and in this respect tau protein is not only subject to changes in length produced by alternative splicing and endoproteolysis, but different types of posttranslational modifications that affect different amino acid residues. Another layer of complexity concerns alternate conformations - “conformers” - of the same covalent structures; in vivo conformers can encompass soluble oligomeric species, ramified fibrillar structures evident by light and electron microscopy and other forms of the protein that have undergone liquid-liquid phase separation to make demixed liquid droplets. Biological concepts based upon conformers have been charted previously for templated replication mechanisms for prion proteins built of the PrP polypeptide; these are now providing useful explanations to feature tau pathobiology, including how this protein accumulates within cells and how it can exhibit predictable patterns of spread across different neuroanatomical regions of an affected brain. In sum, the documented, intrinsic heterogeneity of tau forms and conformers now begins to speak to a fundamental basis for diversity in clinical presentation of tauopathy sub-types. In terms of interventions, emphasis upon subclinical events may be worthwhile, noting that irrevocable cell loss and ramified protein assemblies feature at end-stage tauopathy, whereas earlier events may offer better opportunities for diverting pathogenic processes. Nonetheless, the complexity of tau sub-types, which may be present even within intermediate disease stages, likely mitigates against one-size-fits-all therapeutic strategies and may require a suite of interventions. We consider the extent to which animal models of tauopathy can be reasonably enrolled in the campaign to produce such interventions and to slow the otherwise inexorable march of disease progression.